Cajun justice [compact disc, unabridged] - Patterson, James, 1947-; Axum, Tucker (Hachette Book Group, 2020)
Ex-Secret Service agent Cain Lemaire takes a security job in Tokyo. When he discovers a web of corruption, greed, and extortion, he races to find justice the only way a born-and-raised Cajun can do.